AKAP1 Deficiency Attenuates Diet‐Induced Obesity and Insulin Resistance by Promoting Fatty Acid Oxidation and Thermogenesis in Brown Adipocytes. Issue 6 (1st February 2021) - Ji, Lele; Zhao, Ya; He, Linjie; Zhao, Jing; Gao, Tian; Liu, Fengzhou; Qi, Bingchao; Kang, Fei; Wang, Gang; Zhao, Yilin; Guo, Haitao; He, Yuanfang; et al.
Abstract: Altering the balance between energy intake and expenditure is a major strategy for treating obesity. Nonetheless, despite the progression in antiobesity drugs on appetite suppression, therapies aimed at increasing energy expenditure are limited. Here, knockout of AKAP1, a signaling hub on outer mitochondrial membrane, renders mice resistant to diet‐induced obesity. AKAP1 knockout significantly enhances energy expenditure and thermogenesis in brown adipose tissues (BATs) of obese mice. Restoring AKAP1 expression in BAT clearly reverses the beneficial antiobesity effect in AKAP1 −/− mice. Mechanistically, AKAP1 remarkably decreases fatty acid β‐oxidation (FAO) by phosphorylating ACSL1 to inhibit its activity in a protein‐kinase‐A‐dependent manner and thus inhibits thermogenesis in brown adipocytes. Importantly, AKAP1 peptide inhibitor effectively alleviates diet‐induced obesity and insulin resistance. Altogether, the findings demonstrate that AKAP1 functions as a brake of FAO to promote diet‐induced obesity, which may be used as a potential therapeutic target for obesity. Abstract : In high‐fat‐diet‐treated mice, A kinase anchoring protein 1 (AKAP1) functions as a brake molecule of fatty acid β‐oxidation by recruiting protein kinase A (PKA) and acyl‐CoA synthetase long chain family member 1 (ACSL1) to the outer mitochondrial membrane and inhibiting mitochondrial ACSL1 activity through PKA. AKAP1 elimination enhances mitochondrial ACSL1 activity and increases brown adipose thermogenesis, preventing mice from obesity.